2023
DOI: 10.1128/jvi.01105-23
|View full text |Cite
|
Sign up to set email alerts
|

DAA-mediated HCV cure reduces HIV DNA levels in HCV/HIV coinfected people

Samaa T. Gobran,
Amélie Pagliuzza,
Omar Khedr
et al.

Abstract: The human immunodeficiency virus (HIV) persists in HIV viral reservoirs despite antiretroviral therapy (ART). Hepatitis C virus (HCV) coinfection is associated with increased HIV reservoir size and residual HIV transcription during ART. Herein, we investigated the impact of direct acting antivirals (DAA)-mediated HCV cure on the size/transcriptional activity of the HIV reservoirs and investigated predictors of HIV reservoirs decline in HCV+/HIV+ coinfected individuals. HCV+/HIV+ ( n = 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…A multi-center collaboration within EuroCoord showed that acquiring HCV would result in a temporary decrease in CD4 counts even in chronically virally suppressed PWH [ 6 ]. Conversely, in already HCV-infected PWH, treatment with DAAs resulted in a substantial decrease in HIV DNA levels [ 7 ]. The low-grade inflammation maintained by HIV may have detrimental effects on liver health.…”
Section: Introductionmentioning
confidence: 99%
“…A multi-center collaboration within EuroCoord showed that acquiring HCV would result in a temporary decrease in CD4 counts even in chronically virally suppressed PWH [ 6 ]. Conversely, in already HCV-infected PWH, treatment with DAAs resulted in a substantial decrease in HIV DNA levels [ 7 ]. The low-grade inflammation maintained by HIV may have detrimental effects on liver health.…”
Section: Introductionmentioning
confidence: 99%